Research into reliability issues of an electric power transmission system with a photovoltaic power plan - Kuchansky, V.; Cherkashina, V.; Omelyanenko, G.; Makarov, A.; Hunko, I.; Sabarno, L. (Institute of Renewable Energy, NAS of Ukraine, 2026)
The article provides a study of the reliability of the electric power transmission system with a photovoltaic power plant through a comprehensive analysis of the technical and economic characteristics of cable and overhead power lines. The choice of voltage class for the system under study, which has a radial electrical grid topology with an installed photovoltaic plant at the receiving substation, is justified. In accordance with the selected voltage class, the conductive part of the overhead and cable lines is determined, and the crosssections of the wires and cable cores are checked for acceptable current load conditions. Based on the verification results, the current-carrying part of the over-head transmission line was selected using an ACSR 240/32 mm² conductor, while the cable line was designed with an APvEgP-110 1×240/95 mm² cable. The parameters of the overhead and cable transmission lines were determined, and a comparative analysis of the technological process of electric power transmission in a radial grid was performed using the PowerFactory software package, in particular with respect to voltage deviations in both transmission system variants. It was shown that, in terms of technical performance indicators, the overhead and cable lines are equivalent. Taking this into account, an economic analysis was carried out to substantiate the optimal line option by calculating the cost component of the integral effect of total discounted costs. The results of this analysis indicate that the cable line is 59.4% more expensive than the overhead line. To further justify the feasibility of selecting the line type, a SWOT analysis was conducted, which demonstrated that the project incorporating a cable line is more attractive than the project based on an overhead line. The proposed com-prehensive analysis of the techno-economic characteristics of overhead and cable lines enables a well-grounded decision to be made regarding the selection of the appropriate facility to enhance the reliability of an electric power transmission system with a photovoltaic power plant, provided that the technical parame-ters of the electrical grid are equivalent.

В статті представлено дослідження надійності системи передачі електричної енергії з фотоеле-ктричною станцією шляхом комплексного аналізу техніко-економічних характеристик кабельної та повітряної ліній електропередавання. Обґрунтовано вибір класу напруги досліджуваної системи, що має топологію радіальної електричної мережі з наявною фотоелектричною станцією на приймальній підстанції. Відповідно до обраного класу напруги визначено струмопровідну частину повітряної та кабельної ліній, виконано перевірку перерізів проводів і жил кабелю за умовами допустимого струмового навантаження. Визначено параметри повітряної і кабельної ліній електропередавання та в програмному комплексі PowerFactory здійснено порівняльний аналіз технологічного процесу передачі електричної енергії в радіальній мережі, зокрема відхилення напруги в обох варіантах системи передачі. Показано, що за технічними показниками повітряна й кабельна лінії є рівноцінними. З огляду на це проведено економічний аналіз для обґрунтування оптимального варіанта лінії шляхом розрахунку витратної складової інтегрального ефекту сумарних дисконтованих витрат, за результатами якого встановлено, що кабельна лінія є на 59,4% дорожчою за повітряну. Для уточнення доцільності вибору типу лінії виконано SWOT-аналіз, за результатами якого проєкт із кабельною лінією виявився більш привабливим, ніж проєкт із повітряною лінією. Запропонований комплексний аналіз техніко-економічних характеристик повітряної та кабельної ліній дозволяє прийняти обґрунтоване рішення щодо вибору об’єкта для підвищення надійності системи передачі електричної енергії з фотоелектричною станцією за умови рівноцінних технічних параметрів електричної мережі.
Дослідження питань надійності системи передачі електричної енергії з фотоелектричною станцією
Keywords: renewable energy source; electrical grid; cable line; reliability; overhead line; electric power transmission system; techno-economic characteristics; photovoltaic power plant; відновлюване джерело енергії; електрична мережа; кабельна лінія; надійність; повітряна лінія; система передачі електричної енергії; техніко-економічні характеристики; фотоелектрична станція